Pendekatan Hermeneutika dalam Memahami Kedudukan dan Peran Wanita Muslim di Era Modern - Riva Syifaullana; Hilwa Andini Khairunnisa; Khairunnisa Irmaliya; Abdul Fadhil (Yayasan Al-Afif, 2025)
The position of Muslim women is often perceived rigidly, primarily due to a textualist understanding of Islamic sources. Hermeneutics, with its focus on interpretation, context, and the dialogue between text and reader, offers a path for re-interpretation that is relevant to contemporary social, economic, and cultural challenges. This research aims to identify how the application of hermeneutic principles (such as historicity, context, and fusion of horizons) can lead to a more dynamic, inclusive and just understanding of Muslim women’s right and responsibilities. The findings suggest that through the hermeneutic approach, the role of Muslim women can be interpreted beyond traditional boundaries, acknowledging their leadership capacity, public contribution, and personal autonomy, while adhering to fundamental Islamic values. This approach is essential for bridging the gap between tradition, modernity, and for empowering Muslim women to participate fully in modern society.